2014
DOI: 10.1075/is.15.1.02smi
|View full text |Cite
|
Sign up to set email alerts
|

Infant-directed visual prosody

Abstract: Acoustical changes in the prosody of mothers’ speech to infants are distinct and near universal. However, less is known about the visible properties mothers’ infant-directed (ID) speech, and their relation to speech acoustics. Mothers’ head movements were tracked as they interacted with their infants using ID speech, and compared to movements accompanying their adult-directed (AD) speech. Movement measures along three dimensions of head translation, and three axes of head rotation were calculated. Overall, mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 48 publications
(58 reference statements)
0
20
0
Order By: Relevance
“…We provide a bi-directional mechanistic explanation that involves the organism and its sociolinguistic environment - the ongoing interaction between infants’ perception and maternal scaffolding (Gogate & Hollich, 2010, 2013; Sullivan & Horrowitz, 1983; Yu, Ballard & Aslin, 2005). In general, caregivers coordinate their use of higher pitch, exaggerated intonation contours, elongated speech and longer pauses between utterances (Cooper, Abraham, Berman, & Statska, 1997; Fernald & Simon, 1984; Kitamura & Burnham, 2003) with simultaneous visual mouth movements (Bahrick & Pickens, 1988; Dodd, 1979; Legerstee, 1990; Meltzoff & Kuhl, 1994), more animated head movements and facial expressions (Smith & Strader, 2014; Walker-Andrews, 1997), and gestures using hands and body (Brand, Baldwin & Ashburn, 2002; Brand & Tapscott, 2007). This coordinated information is amodal , invariant , and redundant; the same information conveyed to one sense modality is conveyed to another in the form of a common temporal structure, tempo, rhythm, and spatial colocation (see review by Gogate & Hollich, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We provide a bi-directional mechanistic explanation that involves the organism and its sociolinguistic environment - the ongoing interaction between infants’ perception and maternal scaffolding (Gogate & Hollich, 2010, 2013; Sullivan & Horrowitz, 1983; Yu, Ballard & Aslin, 2005). In general, caregivers coordinate their use of higher pitch, exaggerated intonation contours, elongated speech and longer pauses between utterances (Cooper, Abraham, Berman, & Statska, 1997; Fernald & Simon, 1984; Kitamura & Burnham, 2003) with simultaneous visual mouth movements (Bahrick & Pickens, 1988; Dodd, 1979; Legerstee, 1990; Meltzoff & Kuhl, 1994), more animated head movements and facial expressions (Smith & Strader, 2014; Walker-Andrews, 1997), and gestures using hands and body (Brand, Baldwin & Ashburn, 2002; Brand & Tapscott, 2007). This coordinated information is amodal , invariant , and redundant; the same information conveyed to one sense modality is conveyed to another in the form of a common temporal structure, tempo, rhythm, and spatial colocation (see review by Gogate & Hollich, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Only the positive social events (women speaking in affective positive IDS) were used from Experiment 1. They were judged most appropriate given IDS is highly salient to infants (Cooper & Aslin, 1990; Fernald, 1984; for a review, see Soderstrom, 2007) and it provides exaggerated intersensory information (Bahrick & Todd, 2012; Kubicek et al, 2014; Smith & Strader, 2014). Also, given our focus on assessing developmental change, positive social events were chosen as performance on these trials showed the most improvement with age in Experiment 1 (see Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…Surprisingly, 11‐month‐olds did not respond preferentially to visual‐only versions of ID singing (Costa‐Giomi, 2014), which does not preclude the possibility that infants would do so for natural versions rather than portrayals in the absence of an infant. Mothers produce distinctive facial expressions (Chong, Werker, Russell, & Carroll, ) and head movements (Smith & Strader, ) when they speak to infants, and Experiment 1 revealed that they smile more when singing than when talking to infants. It is possible, then, that infants’ greater interest in audiovisual renditions of maternal singing (Nakata & Trehub, ) stems, in part, from more positive facial displays during such singing.…”
Section: Methodsmentioning
confidence: 99%